Youth, Sport, and Faith: Identity Formation in High School Athletes - Parker, Andrew (Religions, 2023)
It is widely accepted that the transition from youth to adulthood in western industrialized societies brings with it a series of tensions and dilemmas in terms of identity formation. One of the areas where such formational issues often manifest themselves is through the faith journeys of young people. This paper presents empirical evidence from a small-scale qualitative study of one faith–sport initiative—Run the Race Well—a US-based venture which, through an annual retreat program, aims to provide theological support for high school athletes involved in the higher echelons of sport in their age group. Utilizing the “voices” of retreat participants, the paper uncovers some of the issues surrounding the Christian identity of the young people who have participated in the program and explores how the prioritization of lifestyle activities (e.g., education, sport, and faith) has the potential to give rise to particular problems and anxieties. The paper discusses some of the complexities of this prioritization process to reveal how young people seek to navigate and negotiate their identities, both as elite athletes and Christians, and how the tensions and dilemmas of teenage life shape their views of the overall relationship between sport and faith. The paper concludes by suggesting that amidst the wider anxieties of youth transition, intentional investment by others (via theological teaching, sports coaching, and one-to-one, group, and peer mentoring) can provide a catalyst for identity formation and personal/faith development.